Insecticidal action of glycerol monolaurate against the lesser mealworm (Alphitobius diaperinus) and its ecotoxicological effect on Enchytraeus crypticus - Tomasi T.* (2018)
© 2018 Universidade Federal do Rio Grande do Sul. All rights reserved.Background: Alphitobius diaperinus, known as the lesser mealworm, is recognized as a problem for the poultry production sector. Several chemical methods have been employed in an attempt to control it, without successful results. Thus, alternative methods should be considered as an interesting approach to control this type of infestation. A recent study showed that glycerol monolaurate (GML) possesses insecticidal effect against bees. Therefore, the aim of this study was to evaluate, for the first time, the effect of GLM against the larval and adult forms of the lesser mealworm in vitro, and to verify whether GLM treated poultry litter used as soil fertilizer exerts any negative effect on its fauna. Materials, Methods & Results: In vitro tests were performed using three concentrations of GLM: 0.2, 0.4 and 1 mg mL-1, and the number of dead larvae and adults of A. diaperinus was counted on days 0, 2, 5 and 8 post-treatment. Poultry litter was pulverized with 1 mg mL-1 of GML, maintained under controlled conditions for 20 days and revolved every two days. Two ecotoxicological tests were performed using Enchytraeus crypticus. In the first test, GML was applied directly into the soil at doses of 0.5, 1 and 2 mg kg-1 of soil, while the second test used poultry litter as soil fertilizer at concentrations of 0, 2, 4 and 8 tons per hectare. Insecticidal action of GML against larvae and adults of A. diaperinus where only the 1 mg mL-1 concentration showed positive effect. GML caused 100% mortality of larvae two days after the beginning of treatment. Similarly, GML showed high efficacy to control adult forms of A. diaperinus, causing 83 and 90% of mortality on days 5 and 8 post-treatment, respectively. No difference was observed while applying GML directly at doses of 0.5, 1 and 2 mg kg-1 in the TAS when compared to the control group, similarly to what was observed using poultry litter containing 1 mg/m2 of GML at concentrations of 0, 2, 4 and 8 tons per hectare compared to the control group. Discussion: GML treatment exerted larvicidal and insecticidal action in vitro against A. diaperinus, similarly to what was observed by researchers against bees, where this product was able to eliminate 55% of the bees after 120 h of treatment. GML insecticidal mechanism of action is poorly investigated and remains unknown. However, there are evidences regarding its antimicrobial property using Staphylococcus aureus, Streptococcus spp., Enterococcus faecalis, as well as its capacity to inhibit some virulence factors linked to antimicrobial resistance. Some tests have been performed in order to reduce the use of chemical products, as Melaleuca alternifolia (tea tree oil), Ocotea odorifera (popularly known as sassafras) and Eucalyptus viminalis (popularly known as eucalypt) essential oils exerts insecticidal action against the larvae and adults of mealworms. The main chemical used to control A. diaperinus is cypermethrin, a chemical product that can damage the soil fauna due to its intensive utilization. The use of GML did not cause negative effects in the soil fauna, in disagreement other study with GML at concentrations of 50 and 100 μg mL-1 and found negative effects on the soil fauna using adults and juvenile forms of springtails (Folsomia candida) as biomarkers, showing a LD50 of 41 μg mL-1. Based on these evidences, we can suggest that the toxicity of GML to soil fauna is related to the biomarker used to determine the toxicity. Therefore, it is possible to conclude that GML possesses insecticidal action without toxic effects for the soil fauna, demonstrating potential as an alternative method to control the lesser mealworm.